DNA methylation changes in the postmortem dorsolateral prefrontal cortex of patients with schizophrenia - Numata, Shusuke; Ye, Tianzhang; Herman, Mary; Lipska, Barbara K. (Frontiers in Genetics, 2014)
Background: Schizophrenia is a complex psychiatric disorder with a lifetime morbidity rate of 0.5 ―1.0%. The pathophysiology of schizophrenia still remains obscure. Accumulating evidence indicates that DNA methylation, which is the addition of a methyl group to the cytosine in a CpG dinucleotide, might play an important role in the pathogenesis of schizophrenia. Methods: To gain further insight into the molecular mechanisms underlying schizophrenia, a genome-wide DNA methylation profiling (27,578 CpG dinucleotides spanning 14,495 genes) of the human dorsolateral prefrontal cortex (DLPFC) was conducted in a large cohort (n = 216) of well characterized specimens from individuals with schizophrenia and non-psychiatric controls, combined with an analysis of genetic variance at 880,000 SNPs. Results: Aberrant DNA methylation in schizophrenia was identified at 107 CpG sites at 5% Bonferroni correction (p < 1.99 x 10-6). Of these significantly altered sites, hyper-DNA methylation was observed at 79 sites (73.8%), mostly in the CpG islands (CGIs) and in the regions flanking CGIs (CGI: 31 sites; CGI shore: 35 sites; CGI shelf: 3 sites). Furthermore, a large number of cis- methylation quantitative trait loci (mQTL) were identified, including associations with risk SNPs implicated in schizophrenia. Conclusions: These results suggest that altered DNA methylation might be involved in the pathophysiology and/or treatment of schizophrenia, and that a combination of epigenetic and genetic approaches will be useful to understanding the molecular mechanism of this complex disorder.